NEOPROTEROZOIC AGE OF COLLISIONAL METAMORPHISM IN THE TRANSANGARA REGION OF THE YENISEI RIDGE (BASED ON 40Ar/39Ar DATA) - Likhanov I.I.; Kozlov P.S.; Polyansky O.P.; Popov N.V.; Reverdatto V.V.; Travin A.V.; Vershinin A.E. (My University, 2007)
In terms of geodynamics, the Yenisei Ridge is one of the most interesting regions in the southwestern folded framing of the Siberian Craton. Regional structures of the Transangara region of the Yenisei Ridge are traditionally depicted as a NW-extending system of tectonic sheets separated by faults located near the zone of collision of blocks. The collision was responsible for the regional process of heterogeneous (with respect to pressure) metamorphism expressed in the juxtaposition of two (low- and moderate-pressure) facies series. The moderate-pressure collisional metamorphism of the presumably younger stage is locally overprinted on low-pressure metamorphic rocks. Therefore, andalusite is progressively replaced with kyanite, resulting in the formation of new mineral assemblages and deformation structures.
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская